Perengkahan Katalitik Palm Fatty Acid Distillate (PFAD) Menjadi Biofuel Dengan Katalis Abu TKS Variasi Temperatur Dan Berat Katalis - Blesvid, Bloomy; Yelmida, Yelmida; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Technology of catalytic cracking process that has been widely used to process petroleum and  now used to process vegetable oil into biofuel. PFAD is a by-product of refining CPO process which has trigleceryde that can be converted into biofuel equivalent with fuel. PFAD cracking using ash palm empty fruit bunches (PEFB) catalyst with variation temperature and weight of catalyst. The purposes of the research is to obtain the operation condition such as the temperature and weight of catalyst to get the highest yield(%), to know the composition of the product, and to know physical properties product such as density, viscosity, and flash point. Weight of catalyst composition was varied from 0,5% to 2,5% wt with temperature range 350oC to 430 oC, rates of agitation 300 rpm, and the flowrate N2 is 150 ml/minute. Composition product analysed by GC- MS and the result is fractions fuel such as gasoline, kerosene, and diesel. The analysed showing that PFAD cracked into gasoline fraction with the highest yield is 54,3%. Key Words: Ash PEFB, biofuel, catalytic cracking, PFAD